Willingness of returning migrant workers to purchase houses: A case study of 45 villages in Henan Province, China - Yuchan, Wang; Genghe, Gao; Xiaoju, Ning; Yuanzheng, Li; Ning, Niu; Yaqi, Guo (Regional sustainability, 2022)
The willingness of returning migrant workers to purchase houses has an important impact on local urbanization. At present, there are few researches on the willingness of returning migrant workers to purchase houses. The existing researches mostly focus on the perspective of sociology and economics, and few studies are conducted from the perspective of geography. Based on the survey data of 45 villages in Henan Province of China in 2019, this study used binary logistic method to study the influencing factors of the willingness of returning migrant workers to purchase houses. The willingness of returning migrant workers to purchase houses is affected by many factors, such as personal, family, village, and returning factors. Among them, age and returning period are negatively correlated with the willingness of returning migrant workers to purchase houses. Factors such as years of education, years of working, and per capita income of village are positively correlated with the willingness of returning migrant workers to purchase houses. Returning migrant workers in plains and hilly areas are more willing to purchase houses than those in mountainous areas. The formation of the willingness to purchase houses is mainly related to economic foundation, age, marital status, and other factors. Returning migrant workers are becoming more willing to purchase houses, and the expected locations are mainly concentrated in the county seats. In the context of China's high density of rural population and rapid urbanization, more returning migrant workers are expected to purchase houses in cities and towns for the sake of employment, marriage, children's education, and access to public services. As a result, there is an extensive market of potential purchasers, which affects the development of the local urban real estate industry and is of great significance for returning migrant workers to truly integrate into the cities. However, some returning migrant workers still choose to purchase houses in villages, mainly affected by traditional concepts, living habits, and the better development of villages. Therefore, it is of great practical significance to explore the willingness of returning migrant workers to purchase houses, so as to master the flow laws and future behavior of returning migrant workers to purchase houses.